(untitled) (Homoeopathy for All, 2022)
Acne is also known as pimple in the layman terms. Acne is one of the commonest skin disorders – if not the commonest, it has been evident in 70% of population at some stage during their adolescence, occurs mainly due to occlusion of sebaceous gland which may be due hair, sebum, dirt including bacteria and dead skin cells. It’s a chronic inflammatory disease of the pilosebaceous unit. Open pores when get blocked usually present as open comedone (black head) and closed comedone (white head). About 80% of people ages 11 to 30 will have some or the other mild form of acne, and most people are affected by it at some point in their lives. Area affected mostly includes face, arms, chest, and upper back.